2014
DOI: 10.1155/2014/120391
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Liver as a Remote Organ after Renal Ischemia-Reperfusion Injury by Renal Ischemic Postconditioning

Abstract: This study was designed to investigate the protective effects of local renal ischemic postconditioning (POC) on liver damage after renal ischemia-reperfusion (IR) injury. Male rats were divided into three groups  (n = 8). They underwent a right nephrectomy before induction of 45 minutes of left kidney ischemia or sham operation. POC was performed by four cycles of 10 seconds of ischemia and 10 seconds of reperfusion just at the beginning of 24 hours of reperfusion. Then blood and liver samples were collected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Seifi et al [14] evaluated the protective effect of IPC on liver damage after kidney I/R. Rats underwent renal ischemia for 45 minutes and IPC was carried out in four cycles of I/R, each with a 10-second duration.…”
Section: Discussionmentioning
confidence: 99%
“…Seifi et al [14] evaluated the protective effect of IPC on liver damage after kidney I/R. Rats underwent renal ischemia for 45 minutes and IPC was carried out in four cycles of I/R, each with a 10-second duration.…”
Section: Discussionmentioning
confidence: 99%
“…hepatocytes, Von-kupffer cells, extra) in response to injury [36]. recruitment of neutrophils, activates T cells, and induces expression of other cytokines and chemokines such as TNF-α and IL-6 in liver tissue [11,37]. Moreover, other studies showed that following experimental renal IRI in knockout mice for TNF-α or neutralized with TNF-α antibodies displayed reduced hepatic injury after renal IRI [1].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing mortality rate in cases with acute renal injury necessitates designing strategies to assess the effect of renal injury on distant organs [11]. Therefore, several studies [8,[1][2][3][4][5][6][7][8][9][10][11][12][13][14] tried to protect liver from remote injury induced by renal IRI for the prevention and attenuation of acute renal injury related morbidity.…”
mentioning
confidence: 99%
“…Further studies showed that harmful effects of renal I/R are not limited to the kidney, but extend to other organs including liver [6] , lung [7] , brain [8] , heart [9] and gut [10] leading to what is called remote organ injury (ROI), in a process of organ crosstalk by which AKI can lead to multiple organ dysfunction or even failure [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…Humoral and/or cellular factors are thought to be the cause of hepatic injury secondary to I/R. Previous studies have shown that acute kidney injury causes an increase in leukocytic infiltration and induces oxidative stress in the liver resulting in hepatic dysfunction [6,13,14] .…”
Section: Introductionmentioning
confidence: 99%